'SYRIZA and Podemos, we shall overcome'? Left transnational cooperation in times of crisis. (December 2022) - Bortun, Vladimir
The Eurozone crisis and its austerity-centred management opened up a fertile ground for the so-called 'radical left parties' (RLPs) and their anti-austerity agenda. Moreover, it provided a unique opportunity for this party family to enhance its rather underdeveloped transnational cooperation. Sharing several objective and subjective features, SYRIZA (Greece) and Podemos (Spain) – arguably the two most prominent European RLPs today – seemed particularly well-placed to develop a strong transnational cooperation. However, the current literature has hardly addressed whether such expectations have been borne out. Indeed, despite a recently increased interest in the radical left, there are still very few studies focusing on the transnational cooperation among RLPs. Building on documentary research and qualitative elite interviews covering the 2014–2017 period, the article has two main objectives: first, to map the cooperation between SYRIZA and Podemos by identifying the key channels and actors of this process; second, to assess their cooperation over said period, with a focus on the factors fuelling and obstructing it. The article argues that the relationship between the two parties reached its peak around SYRIZA's electoral victory in January 2015 but declined following its deal with the 'Troika' 6 months later, which blatantly contradicted SYRIZA's anti-austerity programme. It is shown that while the main incentives behind their cooperation have been their shared opposition to neoliberalism, the European Union's (EU) reaction to the crisis, and the similarities in their countries' economic situations, the main obstacles hindering that cooperation have been the primacy of national politics and the diverging views on the EU. The findings arguably provide useful insights for the wider left transnational cooperation today, in a time of renewed global capitalist crisis, when such cooperation is perhaps more relevant than ever.